ESTETIKA VISUAL PLAFON BERORNAMEN WAYANG KULIT - Salim Salim (Canthing, 2022)
Wayang Jawa (shadow puppets) in the form of traditional paintings as cultural heritage of the ancestors have also inspired the number of artists who are members of Bunga Rumput in creating works of art with aesthetic value. The efforts of these artists can be read as resistance to the entry of works of art from outside that ignore the character of Indonesia. This study aims to discuss the aesthetics of the visual ceiling works that apply shadow puppet ornaments. Methods of data collection is done by observation and documentation. The results showed that the visual aesthetics of this ceiling product with wayang kulit ornaments seen from unity, harmony, symmetry, balance, and contrast are quite good, although not optimal. Besides that, the visual aesthetics of the ornaments of these ceiling works have not shown good complexity, so the beauty obtained is not optimal. The assessment of visual aesthetics in this work is subjective, so it is very possible that there are different assessments. The conclusion that can be conveyed is that aesthetics can be achieved by elevating the traditional culture of the past and at the same time as a form of appreciation for that culture and being a differentiator in the midst of the rise of Chinese painting in Indonesia. Keywords: aesthetics, ceiling, ornament, wayang, leather